Specifications of Wear of Oils in Two-Fuel Systems - Hönig, Vladimír (Manufacturing Technology Journal, 2018)
Article focuses on the monitoring of motor wear of vehicles powered by a dual-fuel diesel-vegetable oil system. The introductory part focuses on the use of biofuels for combustion engines and tribotechnical diagnostics for wear testing. Analysis of engine oil samples from vehicles with different fuels is carried out. Fuel is diesel fuel, biodiesel and a two-fuel system with two fuels - rapeseed oil and diesel fuel. The abrasion wear of biodiesel is increased. Wear in dual fuel system is within the standard exchange interval in the zone of emergency wear of metallic particles and carbon. The article evaluates the adjustment of the oil exchange interval to limit negative effects on wear surfaces. Shortening the interval to the optimum level for biodiesel is 1/3, for dual fuel system is 1/2. Vegetable oil in engine oil causes a change in the character of lubrication. Shortening the interval to 1/2 is necessary to minimize negative effects.
Keywords: Biofuel; Biodiesel; Engine Oil; Wear Particles; Nomogram the Wear